Percepções de crianças com transtorno do desenvolvimento da coordenação e seus pais/cuidadores sobre a participação na cognitive orientation to daily occupational performance approachtm - Samara de Araujo Costa (2018)
Children with Developmental Coordination Disorder (DCD) have difficulty performing activities that require motor skills, with negative impacts on participation in environments such as home and school, which causes secondary implications, such as little tolerance for frustration and low self-esteem. The Cognitive Orientation to Daily Occupational Performance ApproachTM (CO-OP) has been shown to be effective in the treatment of children with DCD, but most studies do not consider the participants' perception of the intervention. Since it differs from traditional approaches to treatment, it is important to consider the lived experience with the participation in this collaborative intervention, not only by parents/caregivers, but especially by children. Through a qualitative, descriptive and exploratory study, we investigated the perceptions of children with DCD and their parents/caregivers about the therapy process and its effects on the daily occupational performance of children and their families. To achieve this aim, we conducted two studies, one with 14 children and the other with 22 parents/caregivers who completed occupational therapy sessions using either the traditional CO-OP approach (control group) or with added parent coaching (experimental group). For data collection, focus groups were carried out, taking into account the type of participant (child and parents/caregivers) and group (control and experimental). In the first study, we present the perspective of parents/caregivers on the elements of CO-OP and the intervention process. Parents refer to results that go beyond goal achievement, involving changes in the children and themselves. They comment on the challenges of participating in CO-OP, their desire for continuity of the program and refer to coaching sessions as a space for relief and exchange of experiences. Parents/caregivers recognized that with therapy, they learned to cope with their children's difficulties, becoming more patient and able to facilitate learning opportunities. In the second study, children expressed their perceptions about the changes experienced with the CO-OP therapy process and the impact of the outcomes on their lives, recognizing elements of the approach as facilitators of learning. In both studies, parents/caregivers and children highlighted the positive impact of CO-OP on the independence and autonomy of the children to perform daily activities. Giving voice to the children through appropriate resources resulted in a wealth of information about their experiences, which contributes to improve our understanding of the intervention process. The results of this study add evidence to the effectiveness of CO-OP as a treatment for children with DCD.